Green : your place in the new energy revolution - Hoffman, Jane S., 1964-; Hoffman, Michael B., 1950- (New York : Palgrave Macmillan, 2008)
"Green contains the unvarnished truth about the coming energy crisis - and what we can do about it. It is a comprehensive guide to the technologies of renewable energy, for both businesses and homes."--BOOK JACKET.
Introduction : even dogs can see in green -- Green money -- Energy present -- Renewable energy, a primer -- Power playing -- Power to the people -- Fuelish choices -- Creating a renewable industry -- Technologies that don't exist yet -- The global low-carbon economy -- The green standard : best practices -- Conclusion : the green economy.
Includes bibliographical references (p. [237]-244) and index.
Keywords: Environmental policy -- United States -- Citizen participation; Environmental protection -- United States -- Citizen participation; Renewable energy sources -- United States; Green movement -- United States